Expectation and Evaluation of Spouse’s Filial Piety and Marital Satisfaction in China - Gui, Yongxia (Frontiers in Psychology, 2021)
The present study examined the effect of expectation and evaluation of spouse’s filial piety on marital satisfaction among young Chinese couples. We administered scales assessing gender role attitude, marital satisfaction, and expectation and evaluation of spouse’s filial piety on 422 married participants and explored the relationships among these variables. The results showed the following: (1) gender role attitude mediated the relationship between participants’ gender and evaluation of their spouse’s filial piety. There was no significant gender difference in the evaluation of spouse’s filial piety; however, men were more likely to have a traditional gender role attitude, and a traditional gender role attitude leads to lower evaluation of spouse’s filial piety. Furthermore, it was found that the wife’s sibling condition influenced the participants’ expectation and evaluation of spouse’s filial piety as compared to the husband’s; (2) the evaluation of spouse’s filial piety was significantly positively correlated with marital satisfaction; and (3) women’s expectations of their husband’s filial piety moderated this relationship. The positive effects of the evaluation of spouse’s filial piety on marital satisfaction were significantly stronger when they had high expectations in this regard.